Application of Augmented Reality-based Educational Technology to Increase Student Engagement in Elementary Schools - Wa Ode Riniati; Deng Jiao; Sri Nur Rahmi (International Journal of Educatio Elementaria and Psychologia, 2024)
The rapid development of educational technology has significantly influenced teaching and learning practices, particularly in elementary education. Traditional classroom methods often struggle to engage young learners effectively, leading to reduced attention and participation. This study addresses this issue by exploring the application of Augmented Reality (AR)-based educational technology to increase student engagement in elementary schools. The research aims to investigate the impact of AR tools on students’ cognitive and affective engagement, thereby enhancing their overall learning experience. A quasi-experimental design was adopted for this research, involving 120 students from three different elementary schools. The students were divided into experimental and control groups, with the experimental group using AR applications to supplement their learning activities while the control group used conventional teaching methods. Data were collected through observations, pre- and post-intervention tests, and student interviews to measure engagement levels and academic performance. The results indicated a significant increase in engagement and understanding of the subject matter among students who used AR-based tools compared to those in the control group. Specifically, the experimental group demonstrated a 35% higher engagement rate and a 20% improvement in academic performance. Interviews also revealed that students found AR tools more interactive and motivating. In conclusion, the application of AR-based educational technology has a positive impact on student engagement and learning outcomes in elementary schools. The study recommends integrating AR tools in the curriculum to foster a more engaging and effective learning environment for young learners.